Corpus Separatum: Kajian Analitikal Resolusi PBB 1947 untuk Menjadikan Bayt Al-Maqdis Sebagai Zon Antarabangsa - Mohd Nor, Mohd Roslan (Jurnal Usuluddin, 2004)
Islamic Jerusalem, which is known in Arabic as Bayt al-Maqdis, beyond doubt- is very significant to Islam and Muslim. Islamic History has shown that one of the important events took place in Bayt al-Maqdis was the Night Journey of Prophet Muhammad s.a.w. However, since the early 20th century, the land experiences chaos, instability and flux because of the Israel intervention over it. The Leagues of Nations (LN), later on known as United Nations (UN), has made efforts to find the best solution to the conflict between Israel and the original inhabitants of Jerusalem. This paper attempts to explore thoroughly one of the suggested solutions within Resolution 181 (II) with special emphasis on corpus separatum, which had been passed by UN on 29 November 1947.